Arsenophonus apicola sp. nov., isolated from the honeybee Apis mellifera. Issue 8 (5th August 2022) - Nadal-Jimenez, Pol; Siozios, Stefanos; Frost, Crystal L.; Court, Rebecca; Chrostek, Ewa; Drew, Georgia C.; Evans, Jay D.; Hawthorne, David J.; Burritt, James B.; Hurst, Gregory D. D.
Abstract : The genus Arsenophonus has been traditionally considered to comprise heritable bacterial symbionts of arthropods. Recent work has reported a microbe related to the type species Arsenophonus nasoniae as infecting the honey bee, Apis mellifera . The association was unusual for members of the genus in that the microbe–host interaction arose through environmental and social exposure rather than vertical transmission. In this study, we describe the in vitro culture of ArsBeeUS T, a strain of this microbe isolated from A. mellifera in the USA. The 16S rRNA sequence of the isolated strain indicates it falls within the genus Arsenophonus . Biolog analysis indicates the bacterium has a restricted range of nutrients that support growth. In vivo experiments demonstrate the strain proliferates rapidly on injection into A. mellifera hosts. We further report the closed genome sequence for the strain. The genome is 3.3 Mb and the G+C content is 37.6 mol%, which is smaller than A. nasoniae but larger than the genomes reported for non-culturable Arsenophonus symbionts. The genome is complex, with six extrachromosomal elements and 11 predicted intact phage elements, but notably less complex than A. nasoniae . Strain ArsBeeUS T is clearly distinct from the type species A. nasoniae on the basis of genome sequence, with 92 % average nucleotide identity. Based on our results, we propose Arsenophonus apicola sp. nov., with the type strain ArsBeeUS T (CECT 30499 T =DSM113403 T =LMG 32504 T ).